Metal Transition in Sodium–Ammonia Nanodroplets. (29th August 2016) - Hartweg, Sebastian; West, Adam H. C.; Yoder, Bruce L.; Signorell, Ruth
Abstract: The famous nonmetal‐to‐metal transition in Na–ammonia solutions is investigated in nanoscale solution droplets by photoelectron spectroscopy. In agreement with the bulk solutions, a strong indication for a transition to the metallic state is found at an average metal concentration of 8.8±2.2 mole%. The smallest entity for the phase transition to be observed consists of approximately 100–200 solvent molecules. The quantification of this critical entity size is a stepping stone toward a deeper understanding of these quantum–classical solutions through direct modeling at the molecular level.